2019
DOI: 10.1016/j.tbs.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

It’s not all fun and games: An investigation of the reported benefits and disadvantages of conducting activities while commuting

Abstract: Travel-based multitasking, or the performance of activities while traveling, is more feasible than ever before, as the expanding availability of shared ride services and increasing vehicle automation coincide with the ubiquity of portable information and communication technology devices. However, the question of whether, and if so, how these increasingly blurred boundaries between activities are truly helping rather than hurting us is not presently well-understood. Using an attitudinally-rich travel survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…Most of these studies focused on measuring which onboard activities are conducted and explore the factors that influence the engagement in those activities (e.g., Berliner et al, 2015;Frei et al, 2015;Gustafson, 2012;Gripsrud and Hjorthol, 2012;Jain and Lyons, 2008;Kenyon and Lyons, 2007;Lyons and Urry, 2005;Lyons et al, 2007;Ohmori and Harata, 2008;Shaw et al, 2019;Susilo et al, 2012;Tang et al, 2018;van der Waerden et al, 2010;Zhang and Timmermans, 2010). These studies revealed a long list of activities that can be conducted onboard of trains, such as sleeping/snoozing, reading for leisure; working (reading/writing/typing/ thinking), talking to other passengers, window gazing/people watching, playing games, cracking a puzzle, listening to music/radio, phone calls/text messages (work), making phone calls/text messages (personal), watching movie, eating/drinking, entertaining children, romancing, and being bored/anxious.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies focused on measuring which onboard activities are conducted and explore the factors that influence the engagement in those activities (e.g., Berliner et al, 2015;Frei et al, 2015;Gustafson, 2012;Gripsrud and Hjorthol, 2012;Jain and Lyons, 2008;Kenyon and Lyons, 2007;Lyons and Urry, 2005;Lyons et al, 2007;Ohmori and Harata, 2008;Shaw et al, 2019;Susilo et al, 2012;Tang et al, 2018;van der Waerden et al, 2010;Zhang and Timmermans, 2010). These studies revealed a long list of activities that can be conducted onboard of trains, such as sleeping/snoozing, reading for leisure; working (reading/writing/typing/ thinking), talking to other passengers, window gazing/people watching, playing games, cracking a puzzle, listening to music/radio, phone calls/text messages (work), making phone calls/text messages (personal), watching movie, eating/drinking, entertaining children, romancing, and being bored/anxious.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the survey also captured preferences for multitasking while on the job, and we found that this is a significant predictor of tolerance toward waiting and preference for expected waiting. We note as well that there is a growing body of literature on travel-based multitasking (multitasking during travel) which reports that multitasking can improve subjective trip perception and utility across modes in most though not all contexts (Banerjee and Kanafani 2008;Ettema et al 2012;Mokhtarian et al 2015;Rasouli and Timmermans 2014;Rhee et al 2013;Russell 2012;Shaw et al 2019;Susilo et al 2012), findings that are echoed theoretically and empirically in the wait time literature under the parlance of equipped or distracted waiting (Maister 1985;Pruyn and Smidts 1998).…”
Section: Discussionmentioning
confidence: 73%
“…distraction) and affective (e.g. interfering with trip enjoyment) 1 3 disadvantages (Shaw et al 2019). Because the relationships between waiting attitudes and many of these variables have rarely (if ever) been detailed in the literature, this comprehensive overview is a useful contribution toward understanding how a wide array of both general and transportation-related attitudes, preferences, and behaviors relate to waiting attitudinal constructs.…”
Section: Resultsmentioning
confidence: 99%
“…Ohmori and Harata 2008); (2) the number of activities performed while traveling, controlling for socio-economic and mode attributes (e.g. Zhang and Timmermans 2010;Tang et al 2018); (3) the impact of travel-based multitasking on the subjective evaluation of trip experience (Ettema et al 2012;Susilo et al 2012;Rhee et al 2013;Rasouli and Timmermans 2014;Mokhtarian et al 2015;Shaw et al 2019;Singleton 2018); and (4) the influence of a multitasking-friendly travel experience on mode choice (Zheng et al 2016;Malokin et al 2019). Keseru and Macharis (2018) have compiled a comprehensive review of travel multitasking studies to date.…”
Section: Impact Of Activities While Traveling On Mode Choicementioning
confidence: 99%